(untitled) (Medico Legal Update, 2020)
Introduction. Osteoarthritis is a common condition that affects elderly people, especially knee osteoarthritis. It can cause pain, muscle weakness, imbalance and low functional activity of elderly people. Knee osteoarthritis not only affects muscles in the knee joint area but also those in the hip joint. To improve symptoms of knee osteoarthritis, strengthening exercise is often conducted only on muscles in the knee joint area, but not muscles in the hip area. This study aimed to compare the effect of strengthening exercise conducted in knee joint muscles only with the strengthening exercise in both knee and hip muscles on pain, strength, balance and functional activity. Method. A pre- and posttest design was chosen as the design of this study. Two groups were formed in this study. Group 1 received strengthening exercise on knee joint muscles only and Group 2 received strengthening exercise on knee joint and hip joint muscles. This study was conducted in Prima Physio Clinic for Group 1 and Tajuddin Chalid Hospital, Makassar for Group 2. On each group, there were 10 subjects with osteoarthritis. The strengthening exercise was conducted for 3 times a week for 4 weeks. The outcome measure used was numeric pain rating scale (NPRS), manual muscle strength (MMT), Berg balance scale (BBS) and Western Ontario McMaster (WOMAC). Manual muscle strength was measured in all major muscles of the joints: iliopsoas, gluteus, tensor fascia lata, quadriceps and hamstring. Results. The statistical analysis was conducted using Wilcoxon and Mann Whitney tests. In group 1 analysis, pain, balance, functional activity, and all major muscle strengths were found to be a statistically significant difference between baseline and 4 weeks post-exercise. In group 2 analysis, pain, muscle strength, balance, and functional activity were found to be a statistically significant difference (p<0.05). The comparison between the two groups showed statistically significant differences in all muscle group strength except for hamstring. Pain, balance, functional activity and hamstring strength were not statistically significantly different between the groups. Conclusion. From the results, we concluded that the strengthening program for both knee and hip muscles is recommended than only to the affected joint muscles.